Education and Training Management of the Fashion Design Upgrading Program at Center for Vocational and Productivity Training (BBPVP) Semarang - Sulistian, Neni; Sutarto, Joko (Jurnal Penelitian Pendidikan, 2025)
The Semarang Vocational Development and Productivity Center (BBPVP) is a leading center in the field of Fashion Technology and is the only work unit that organizes a Fashion Design Upgrading program. This program aims to improve the competence of instructors in the field of design that continues to evolve in line with changing industry forecasting trends. This study aims to describe and analyze the management of the fashion design upgrading program at BBPVP Semarang, which includes aspects of planning, implementation, and evaluation. The research uses a qualitative approach with a case study method. Data collection techniques include in-depth interviews, participatory observations, and documentation, and data validity are strengthened through source triangulation involving structural officials, administrative employees, instructors, and trainees. The results of the study show that program planning is carried out regularly through needs analysis at the institution, position, and individual levels with reference to SKKNI. The implementation of the program pays attention to the readiness of facilities, instructors, and curriculum that are relevant to the latest industry trends. Evaluation is carried out through participant feedback, assessment of training results, and follow-up for program improvement. The conclusion of this study is that the management of upgrading programs is carried out professionally and sustainably with a competency-based approach and adequate resource support. It is recommended that this program continue to be developed through advanced training for instructors, strengthening implementation management, improving the technical and non-technical competencies of participants, and becoming a reference for further research.